Tilting of continental interiors over asource of dynamic topography : Late Cretaceouserosion of the South African plateau - (:unkn) unknown (My University, 2014)
New sedimentary flux data confirm the observation that a large pulseof erosion affected the South African Plateau in the late Cretaceous.This episode of rapid erosion (less than 30 Myr) is likely to be relatedto a major uplift phase that is apparently difficult to reconcile witha possible mantle origin, namely the presence of low density body inthe underlying mantle causing flow and dynamical uplift of the continent.Given its size, the growth and rise of this so-called "African superswell"is likely to have taken one to several hundred million years.Here we demonstrate by using a simple model for fluvial erosion thattilting of the continent as it rides over a wide source of dynamic topographycan not only cause uplift of the plateau but also lead to substantialerosion of large surface areas in a relatively short amount of time, becausethe tilting produces a continental-scale drainage re-organization.We show that embedding a lithological contrast, such as the one thatmight have existed between a thick layer of Karoo volcano-clastic sedimentsoverlying basement, greatly amplifies the rate of erosion (and sedimentation)during the tilting episode.We demonstrate that our scenariois consistent with paleogeographic reconstructions of the position of theAfrican continent with respect to the African superswell, the temporaland spatial evolution of kimberlite eruptions across southern Africa andthe past and present-day highly asymmetrical drainage geometry.
Keywords: African Research